Natural hazards Disasters and Agricultural Impact: - Technical Centre for Agricultural and Rural Cooperation; Inter-American Institute for Cooperation on Agriculture (Technical Centre for Agricultural and Rural Cooperation, 2010)
Media Tool Kit 1: Natural hazards are “naturally occurring physical phenomena” or risk elements inherent in the natural environment; an inevitable part of life on earth